Evaluation of the applicability of hospital-affiliated green spaces to patient recovery using the entropy weight method and grey relational analysis - Yuan, Wei; Yang, Maopeng; Liu, Dan; Fu, Xingyuan; Yu, Lei; Wang, Kun (Frontiers in Public Health, 2024)
Hospital affiliated green spaces can help patients recover and recover their physical functions, promote physical and mental relaxation, enhance health awareness, and improve overall health. However, there are still significant questions about how to scientifically construct hospital affiliated green spaces.This study examines the impact of hospital green spaces on patient rehabilitation through scientific evaluation methods, providing reference for the scientific construction of hospital affiliated green spaces.Applicability evaluation was conducted on the affiliated green spaces of three hospitals in Harbin. An evaluation system covering plants, space, accessibility, rehabilitation functions, and promotional and educational functions has been constructed. The entropy weight method is used to determine the weight of indicators, and the grey correlation analysis method is used to evaluate the suitability of green space for patient rehabilitation. The experimental results showed that the landscape accessibility index had the highest weight (0.3005) and the plant index had the lowest weight (0.1628), indicating that caring for special needs is the foundation of hospital landscapes, and plants have subtle and long-term effects on physical and mental health. In the evaluation of the rehabilitation applicability of the affiliated green spaces of various hospitals, the second hospital has the highest grey correlation degree (0.8525), followed by the tumor hospital (0.5306) and the fifth hospital (0.4846). It can be seen that the green space of the second hospital has high applicability for patient rehabilitation, but the green space of the tumor hospital and the fifth hospital needs to be improved and developed. The three hospitals are relatively reasonable in terms of factory configuration and spatial layout, but insufficient consideration is given to the accessibility and details of landscape design. Landscape restoration, education, and scientific functions can be improved;There are few types of outdoor activities; Insufficient road safety. In summary, hospital green spaces should follow the principles of "appropriate scale, complete functions, and entertainment", integrate rehabilitation and publicity functions, increase outdoor activities, and design roads and facilities that meet the level of happiness.